2010
DOI: 10.1111/j.1600-0587.2009.06037.x
|View full text |Cite
|
Sign up to set email alerts
|

Integrating physiology, population dynamics and climate to make multi‐scale predictions for the spread of an invasive insect: the Argentine ant at Haleakala National Park, Hawaii

Abstract: Mechanistic models for predicting species’ distribution patterns present particular advantages and challenges relative to models developed from statistical correlations between distribution and climate. They can be especially useful for predicting the range of invasive species whose distribution has not yet reached equilibrium. Here, we illustrate how a physiological model of development for the invasive Argentine ant can be connected to differences in micro‐site suitability, population dynamics and climatic g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
48
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(50 citation statements)
references
References 64 publications
1
48
0
1
Order By: Relevance
“…Climatic suitability sets the abiotic conditions that allow species to establish and spread, and climate matching has been identified as a key factor for invasion of many invasive species (9,30). This is especially true for the Argentine ant, whose occurrence at regional scales is highly constrained by temperature and humidity (25,26,31,32). At local scales, establishment by the Argentine ant in climatically favorable areas is also favored by anthropogenic factors (33,34 In its native range, the abundance and impact of the Argentine ant may be constrained by the presence of highly dominant native ant species in the same subfamily (Dolichoderinae) (18).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Climatic suitability sets the abiotic conditions that allow species to establish and spread, and climate matching has been identified as a key factor for invasion of many invasive species (9,30). This is especially true for the Argentine ant, whose occurrence at regional scales is highly constrained by temperature and humidity (25,26,31,32). At local scales, establishment by the Argentine ant in climatically favorable areas is also favored by anthropogenic factors (33,34 In its native range, the abundance and impact of the Argentine ant may be constrained by the presence of highly dominant native ant species in the same subfamily (Dolichoderinae) (18).…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have examined the distribution and dispersal pathways of this invasive ant (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22) and described the range limits at regional and global scales (20,(23)(24)(25)(26)(27)(28). However, most of these studies relied on simple environmental niche models or described the current distribution of the species using only partial records.…”
mentioning
confidence: 99%
“…Thus, there is some probability that the species currently occupying zones that will have novel climates may be able to adapt to those new conditions in situations of limited competition from species more tolerant of those new conditions. The Australian study however also establishes an additional danger of climate change, that being the concomitant influx and flourishing of invasive plants (Hellmann et al, 2008;Dale et al, 2009;Dukes et al, 2009;Hartley et al, 2010). Also important is the physiological impacts on plant establishment and growth if temperatures increase greatly (as projected under HADhi) while precipitation changes little, resulting in more evaporative loss, and leading to greater physiological stress on the biota (Allen et al, 2010).…”
Section: Novel Climatesmentioning
confidence: 97%
“…Modeling techniques have frequently been used to determine the spread of invasive insects under current environmental conditions [59,60] and under the influence of climate change [32,61,62]. The current study has shown that the use of modeling techniques, particularly combined methods, allows the prediction of potential current and future environmental suitability for an invasive insect, BMSB, in a novel environment, i.e., New Zealand.…”
Section: Discussionmentioning
confidence: 93%